Forest resources of Kyrgyzstan and the problems of their conservation and complex using (Journal of Geography and Environmental Management, 2016)
In this article was shown the role and importance of forest resources in maintaining the ecological and socio-economic al stability in Kyrgyzstan. Also the geographical features of the country, protection and development of forests in the region and the basic directions of their integrated use were viewed.
Keywords: forest resources; mountainous terrain